Conceptual Synthesis of Teachers' Etiquette (At-Tibyan) and The Four Pillars of Professional Teacher Competency: A Systematic Literature Review - Gusti Bayu Mandastana (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
Islamic education in this era of disruption faces a double challenge: the demand for complex professional competencies and the moral degradation of students. Law No. 14 of 2005 has established four pillars of teacher competency, but this framework is often interpreted administratively and has not touched on the deeper ethical-spiritual foundations. This study aims to revitalize the concept of teacher competency by synthesizing the values of adab mu'allim from the book At-Tibyan by Imam An-Nawawi into modern teacher competency standards. This study uses a qualitative method with a Systematic Literature Review (SLR) approach. Data were collected through documentation of classical texts and indexed journal articles (2015-2025), then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results show a strong overlap between the values of At-Tibyan and the Teacher and Lecturer Law. Personal Competence is strengthened by sincerity and muraqabah; Social Competence is deepened by rifq (gentleness); and Professional Competence is perfected by the concepts of itqan (validation of the chain of transmission of knowledge) and hirshu (fighting spirit). This integration offers a “Complete Teacher” paradigm who is not only technically professional but also has spiritual authority in shaping students' character in the digital age.